2008
DOI: 10.1063/1.2949081
|View full text |Cite
|
Sign up to set email alerts
|

Transition layers at the SiO2∕SiC interface

Abstract: The electrical performance of SiC-based microelectronic devices is strongly affected by the densities of interfacial traps introduced by the chemical and structural changes at the SiO2∕SiC interface during processing. We analyzed the structure and chemistry of this interface for the thermally grown SiO2∕4H-SiC heterostructure using high-resolution transmission electron microscopy (TEM), Z-contrast scanning TEM, and spatially resolved electron energy-loss spectroscopy. The analyses revealed the presence of dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
112
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(127 citation statements)
references
References 18 publications
12
112
3
Order By: Relevance
“…Going from SiC to SiO 2 across the interface, the C/Si (O/Si) ratio decreases (increases) gradually without any observable enrichment in any of the elements. In particular, no C-rich area is detected in the SiC or in the bulk SiO 2 as it was previously reported [3][4][5][6][7] . From these profiles, a region of continuously varying composition including the three elements (Si, C and O) named transition layer (TL)…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…Going from SiC to SiO 2 across the interface, the C/Si (O/Si) ratio decreases (increases) gradually without any observable enrichment in any of the elements. In particular, no C-rich area is detected in the SiC or in the bulk SiO 2 as it was previously reported [3][4][5][6][7] . From these profiles, a region of continuously varying composition including the three elements (Si, C and O) named transition layer (TL)…”
Section: Resultssupporting
confidence: 60%
“…This degradation was related to electrically active defects at the SiC/SiO 2 interface, such as C clusters [3,4] and/or changes in the C/Si ratio across the SiC/SiO 2 interface. They were observed by different transmission and scanning transmission electron microscopy (TEM and STEM, respectively) techniques, such as high resolution transmission electron microscopy (HRTEM), Z-contrast imaging [5,6] and Electron Energy Loss Spectroscopy (EELS) [7]. On the other hand, these compositional variations were not observed in later works.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Recently, high-resolution TEM, Z-contrast scanning TEM, and spatially resolved EELS studies have revealed a transition layer (∼3 nm) at the interface due to the formation of a ternary Si-C-O phase. [34][35][36] The results indicated that the presence of a transition layer at the SiO 2 /SiC interface could lead to the mobility degradation. On the contrary, Watanabe et al suggested that an interfacial transition layer should be ruled out as a cause of electrical degradation.…”
Section: Introductionmentioning
confidence: 94%
“…Recent works by Zheleva et al [ 130 ] and by Biggerstaff et al [ 131 ], based on a nanoscale characterization using high resolution TEM and EELS, definitively correlated the existence of a "transition layer" on both sides of the SiO 2 /SiC interface with the electrical properties of the SiO 2 /SiC interface. In particular, the structural degradation (amorphization) observed in the top few atomic layers of SiC and the presence of this interfacial transition region was associated to changes in the SiO 2 and SiC stoichiometry.…”
Section: Interface Transport Properties In the Sio 2 /Sic Systemmentioning
confidence: 99%